Charge Characteristics and Cation Exchanges Properties of Hilly Dryland Soils Aceh Besar, Indonesia - Sufardi Sufardi; Teti Arabia; Khairullah Khairullah; Karnilawati Karnilawati; Sahbudin Sahbudin; Zainabun Zainabun (Aceh International Journal of Science and Technology)
Soil surface charge and cation exchange are important parameters of soil fertility in tropical soils. This study was conducted to investigate characteristics of surface charges and cation exchanges on four soil orders of the dryland in  Aceh Besar district. The soil order includes Entisols Jantho (05o16’58.41” N; 95o37’51.82” E), Andisols Saree (05o27'15.6" N; 95o44'09,1" E), Inceptisols Cucum (05º18’18,37” N; 95º32’48,04” E), dan Oxisols Lembah Seulawah (05o27’19,4” N; 95o46’19,2” E). The charge characteristics of surface charge are evaluated from the parameter of DpH (pHH2O-pHKCl), variable charge (Vc), permanent charge (Pc), and point of zero charges (PZC). In contrast, cation exchange properties are evaluated from several soil chemical properties, such as soil organic matter (SOM), base saturation (BS), cation exchange capacity (CEC), and effective CEC (ECEC). The results show that the four pedons of soil in the hilly dryland of Aceh Besar include a variable charge because it has a PZC, which is characterized by a negative surface charge with a PZC of pHH2O and has CEC dependent soil pH. PZC value varies from 3.21 – 5.26 and sequentially PZC Andisols Oxisols Entisols Inceptisols. The total CEC value differs considerably from ECEC and the sum of cations. CEC total of the soils varies from 12.8 – 34.4 cmol kg-1, whereas the ECEC values vary from 2.72 – 8.66 cmol kg-1. The highest variable charge percentage is found in Andisols Saree. In contrast, the highest permanent charge is found in Inceptisols Cucum and is positively correlated with pHH20, PZC, CEC, and sums of cations or ECEC. Improving soil quality in hilly dryland soils in Aceh Besar District can be done by decreasing the PZC status of soils with organic amendments and fertilizers or increasing the pH by using liming.